"Hot" in Plasmonics: Temperature‐Related Concepts and Applications of Metal Nanostructures. Issue 1 (26th November 2019) - Kuppe, Christian; Rusimova, Kristina R.; Ohnoutek, Lukas; Slavov, Dimitar; Valev, Ventsislav K.
Abstract: Recent advances in nonlinear optics, hot electrons for renewable energy (e.g., solar cells and water‐splitting), acousto‐optics, nanometalworking, nanorobotics, steam generation, and photothermal cancer therapy are reviewed here. In all these areas, one of the key enabling properties is the ability of metallic nanoparticles to harvest and control light at the subwavelength scale by supporting coherent electronic oscillations, called localized surface plasmon resonances (LSPRs). Various physical properties and potential areas of application emerge depending on the decay mechanism of the LSPR and, especially, depending on the considered timescale. The field of plasmonics has mainly been associated with manipulating electromagnetic near‐fields at the nanoscale, where absorption is an obstacle. However, plasmonic absorption leads to a stream of temperature‐related phenomena that have only recently attracted significant attention. The goal of this review is to highlight exciting new areas of research (such as nanorobotics, nanometalworking, or acousto‐optical techniques) and to survey the most recent progress in more established areas (such as hot electrons, photothermal therapy, and plasmonic steam generation). To set each research area in context, the text is organized around the thermal cycle of the nanoparticles. Abstract : Upon illuminating plasmonic nanoparticles, electromagnetic hotspots enhance the nonlinear optical processes for advanced imaging applications. Hot electrons find applications in solar cells and water splitting. Lattice heating generates phonons and enables nanometalworking. Environment heating enables applications in photothermal therapy, magnetic storage, and nanorobotics.